Evaluation of the Teaching Industry Program in Developing the Entrepreneurial Spirit of Graphic Design Students - Pertiwi, Annisa; Masunah, Juju; Prawira, Nanang Ganda; Karyono, Tri (JTP - Jurnal Teknologi Pendidikan, 2024)
The creative industry in the hospitality sector faces a huge challenge to innovate in the digital era. The entrepreneurial competence of vocational students is important to meet the needs of the dynamic world of work. This study aims to evaluate the implementation of the Teaching Industry program in developing the entrepreneurial skills of students of the Diploma Program in Graphic Design, Widyatama University through a case study at the Malaka Hotel Bandung for the 2022–2024 period. This Teaching Industry program is designed using the Work-Based Learning approach  to provide real work experience, Experiential Learning for hands-on learning, Collaborative Learning to train teamwork, and Project-Based Learning to complete tasks in the field of digital marketing, such as content planning, graphic design, photography, videography, and social media management. This study uses a mixed method, with a qualitative approach through interviews, observations, and document analysis (logbook, internship report, work presentation, and performance evaluation), as well as a quantitative approach through questionnaires and evaluation of supervisors. The results of the study showed the development of student entrepreneurship indicators, namely: 1) leadership collaboration and teamwork (88%), 2) motivation and confidence in achievement (82%), 3) initiative and courage to take risks (76%), and 4) independence and responsibility (70%). Overall, the program recorded a 79% success rate. Of the 17 students who participated, 3 of them were successfully recommended as contract employees, including 1 student who was recruited as a member of the Malacca Hotel Digital Marketing team. This program is effective in improving digital marketing technical skills as well as teamwork, leadership, and project management skills relevant to the needs of the creative industry.